The effect of live demonstration and flipped classroom with continuous formative assessment on dental students’ orthodontic wire-bending performance - Saritha Sivarajan; Eunice Xinwei Soh; Nor Nadia Zakaria; Yasmin Kamarudin; May Nak Lau; Aufa D. Bahar; Norhidayah Mohd Tahir; Wan Nurazreena Wan Hassan; Mang Chek Wey; Siti Adibah Othman; Roziana M Razi; Zahra Naimie (BMC Medical Education, 2021)
Abstract Background Wire-bending skills is commonly taught through live demonstrations (LD) though flipped classroom (FC) method has gained popularity. Continuous formative assessment promotes personalised learning via closely monitored progress, with the identification of students’ strengths and weaknesses. This study aims to evaluate the effects of LD and FC teaching methods, supplemented with continuous formative assessment, on dental students’ learning of wire-bending skills for six types of removable orthodontic appliance components. A deeper understanding of the relative effectiveness between LD and FC teaching methods can help identify the most appropriate method to achieve student learning objectives, which is especially important given the current Covid-19 pandemic. Methods Forty third-year undergraduate dental students were randomly assigned into FC (n = 20) or LD (n = 20) cohort. Each student attended six teaching sessions, each to teach students’ competency in fabricating one type of wire component, for a total competency in fabricating six wire components over the course of six teaching sessions. Either LD or FC teaching methods were used. After each session, wire assignments had to be submitted. Wire assignments were then evaluated using a blinded wire-bending assessment protocol. As part of their formative assessment, the assessment results were distributed to students, lecturers, and technicians before the next session. After the first session (T0) and at the end of all six sessions (T1), students completed a self-reported questionnaire. Results The mean wire-bending scores for FC were significantly higher than LD for two of the six assignments, namely the Adams clasp (p < 0.01) and Z-spring (p = 0.03). Scores for both LD and FC increased significantly over time, which may be attributed to formative assessment. There was no statistically significant correlation between wire-bending scores and video usage. Students were satisfied with both teaching methods, according to T0 and T1 questionnaires. Conclusions Both LD and FC are equally effective in transferring practical orthodontic wire-bending skills and well-received by students. Continuous formative assessment may have enhanced students’ learning of orthodontic wire-bending skills. Further studies with control group are recommended to investigate the effect of formative assessment on teaching practical dental skills.